An Analysis on Students’ Problems in Writing a Recount Text at An Analysis on Students Problems in Writing Recount Text at The Eleventh Grade Students of Senior High School - Putri Sundari, Febby Salsabila; Ayu, Citra; Hardi, Vitri Angraini (Institut Agama Islam Negeri Palopo, 2023)
This research is motivated by the low ability of students in writing recount text at SMAN 2 Kuok. This study aims to determine students’ problem in writing recount text in class XI students at SMAN 2 Kuok. This study uses a qualitative research design. Class XI MIA consists of 21 students. The sampling technique used was purposive sampling. The instrument used in this research is a questionnaire. Data were analyzed by describing students problems in writing recount text. Based on the result of the questionnaire, the researcher found that students had 4 problems in writing reount text such as vocabulary, organization, mechanic and grammar. Based on the results of the analysis of the questionnaire 81% of students had difficulty using grammar while 56,2% of students had difficulty understanding concept of vocabulary.